The potential effects of transport costs on unemployment in South Africa - De Lange, Kieran (My University, 2014)
The relationship between transport costs and unemployment in South Africa is under researched, mostly due to a lack of appropriate data. However, two surveys—the National Income Dynamics Study (NIDS) and the Labour Market Entry Survey (LMES)—have recently collected information on transport costs. This thesis uses these new sources of data to examine three aspects of the relationship between transport costs and unemployment in South Africa. The first is the relationship between transport costs and the probability of searching for employment. The second is the relationship between reservation wages and transport costs. The third is the relationship between transport premiums and transport costs, with a focus on commute times as a proxy for transport costs. This research shows: the negative correlation between job search and transport costs; a positive correlation between median transports costs and reservations wages for jobs that are far; negative correlation between transport premiums and transport costs.